Conflict Resolution between Nahdlatul Ulama and Muhammadiyah Congregations in Tumpak Rejo Hamlet, Ponorogo Regency - Elsa Nurrohim Safitri; Anwar Mujahidin (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2022)
The two largest and most powerful socio-religious groups in Indonesia are Nahdlatul Ulama (NU) and Muhammadiyah. They have members from all over the country and have different religious views regarding some religious rituals aspect. These differences often give rise to friction in the realm of social life. This study aims to describe the conflict resolution between NU and Muhammadiyah in Tumpak Rejo Hamlet, Tambang Village, Pudak District, Ponorogo Regency. This study used a qualitative approach, and the data were obtained from interviews and observations with the residents of Tumpak Rejo Hamlet. This study shows that the conflict between NU and Muhammadiyah members also stems from differences in views about religious practices that take place in society. The role of the village government and community leaders succeeded in producing conflict resolution between the two community groups and, at the same time, creating tolerance and mutual respect between the two. This study concludes that cultivating an attitude of tolerance, a sense of togetherness, and mutual respect between communities is a resolution model that can overcome religious conflicts in society.